2014
DOI: 10.1039/c4cc04731a
|View full text |Cite
|
Sign up to set email alerts
|

A single molecular probe for multi-analyte (Cr3+, Al3+and Fe3+) detection in aqueous medium and its biological application

Abstract: An ESIPT based fluorescent sensor 1 was developed, which could selectively detect and differentiate trivalent metal ions Cr3+, Al3+ and Fe3+ in aqueous. The cell imaging experiments confirmed that 1 can be used for monitoring intracellular Cr3+ and Al3+ levels in living cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(51 citation statements)
references
References 62 publications
1
49
0
1
Order By: Relevance
“…An ESIPT based fluorescent sensor was also prepared by Wang et al for effectively detecting trivalent metal ions Cr 3+ in aqueous medium. The cell imaging experiments further confirmed that the ESIPT based fluorescent sensor can be used for monitoring intracellular Cr 3+ levels in living cells [21].…”
Section: Introductionsupporting
confidence: 58%
“…An ESIPT based fluorescent sensor was also prepared by Wang et al for effectively detecting trivalent metal ions Cr 3+ in aqueous medium. The cell imaging experiments further confirmed that the ESIPT based fluorescent sensor can be used for monitoring intracellular Cr 3+ levels in living cells [21].…”
Section: Introductionsupporting
confidence: 58%
“…Probe 15 was shown to be effective at monitoring intracellular Cr 3+ and Al 3+ levels in human mesenchymal stem cells. 57…”
Section: Cobalt (Co 2+ )mentioning
confidence: 99%
“…Measurement conditions: pH = 7.5. N-terminus of a Tat (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61) peptide that corresponded to the binding domain of the HIV-1 Tat protein. These ESIPT labelledpeptides produced dramatic ratiometric changes in the fluorescence intensity and could be used to investigate hydration levels in the vicinity of the peptide/oligonucleotide complex, revealing a solvation trend that decreases in the following order short ssDNAs c long ssDNAs 4 DNA hairpins 4 dsDNAs.…”
Section: Esipt Probes For Interrogating Biomolecular Interactionsmentioning
confidence: 99%
“…With rapid development of international globalization and industrialization, heavy-metal pollution has attracted much more attention in the field of environment and human health. [1,2] Due to the non-biodegradation nature of mercury ion (Hg 2+ ), it can only be diluted but not to be destroyed. [3] Long term accumulation of this metal in organisms can destroy DNA, inhibit ligand-receptor interactions, disable normal functions of liver and kidney, disrupt the homeostasis of immune system, and even lead to death.…”
Section: Introductionmentioning
confidence: 99%